Removal of Metal Ions in Spin-on Hardmask Using Functionalized Porous Silica Adsorbents - Won Kim; Kiseok Lee; Hyosik Kim; Mingi Choi; Suk-Koo Hong; Ji Eun Lee (Applied Sciences, 2025)
The ongoing miniaturization of semiconductor devices necessitates continuous advancements in lithographic processes, which are critical for high-precision circuit formation. To prevent substrate damage during the etching step, a spin-on hardmask (SOH) layer is often introduced between the photoresist (PR) and the substrate. However, residual metal ions in SOH solutions can adversely affect integrated circuit performance, underscoring the need for efficient and chemically compatible removal strategies. This study investigates the adsorption of metal ions (Al3+, Cr3+, Cu2+, Fe3+, Ni2+, and Ti4+) from SOH solutions using mesoporous silica materials—MCM-41 and SBA-15—functionalized with various groups (–OH, –NH2, –SH, and –CH3). Adsorption performance was evaluated under solvent-only, monomer-containing, and polymer-containing conditions. Among the tested materials, amine-functionalized mesoporous silica exhibited the highest adsorption efficiency, with SBA-15-NH2 showing relatively effective and uniform performance in polymer-containing systems. Isotherm analysis supported a monolayer chemical adsorption mechanism, suggesting the significance of surface functional groups in the adsorption process. These findings demonstrate the potential of functionalized mesoporous silica as a promising candidate for trace metal ion removal in semiconductor manufacturing, offering enhanced yield and improved process reliability.